Pengaruh Kualitas Pelayanan, Kualitas Produk Dan Harga Terhadap Kepuasan Konsumen Warung Tepi Setu - Susilowati, Ratna; B , Apriana Anggraeni; Drajat, Fardan (Politeknik Negeri Ambon, 2024)
This scientific research aims to analyze the influence of product quality, service quality and price on consumer satisfaction at Warung Tepi Setu (case study of consumers at Warung Tepi Setu, Jalan Citayam. Cipayung, Depok City). The data collection method used was a questionnaire with a sample size of 100 respondents who are consumers of Warung Tepi Setu. The analysis methods used are Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, Multiple Linear Regression Analysis, Partial Test (t), Simultaneous Test (F) and Coefficient of Determination Test (R2). The testing tool used is SPSS v.22. The results of research using the Partial Test (T) show that the variables of product quality, service quality and price partially influence consumer satisfaction. Through the Simultaneous Test (F), it shows that the variables product quality, service quality and price simultaneously influence consumer satisfaction. Meanwhile, the Coefficient of Determination Test (R2) shows that product quality, service quality and price have a 26.2% effect on consumer satisfaction. Keywords: Service Quality, Product Quality, Price, Consumer Satisfaction